Population pharmacokinetics of colistin and the relation to survival in critically ill patients infected with colistin susceptible and carbapenem-resistant bacteria. (December 2020) - Kristoffersson, A.N.; Rognås, V.; Brill, M.J.E.; Dishon-Benattar, Y.; Durante-Mangoni, E.; Daitch, V.; Skiada, A.; Lellouche, J.; Nutman, A.; Kotsaki, A.; Andini, R.; Eliakim-Raz, N.; et al.
Abstract: Objectives: The aim was to analyse the population pharmacokinetics of colistin and to explore the relationship between colistin exposure and time to death. Methods: Patients included in the AIDA randomized controlled trial were treated with colistin for severe infections caused by carbapenem-resistant Gram-negative bacteria. All subjects received a 9 million units (MU) loading dose, followed by a 4.5 MU twice daily maintenance dose, with dose reduction if creatinine clearance (CrCL) < 50 mL/min. Individual colistin exposures were estimated from the developed population pharmacokinetic model and an optimized two-sample per patient sampling design. Time to death was evaluated in a parametric survival analysis. Results: Out of 406 randomized patients, 349 contributed pharmacokinetic data. The median (90% range) colistin plasma concentration was 0.44 (0.14–1.59) mg/L at 15 minutes after the end of first infusion. In samples drawn 10 hr after a maintenance dose, concentrations were >2 mg/L in 94% (195/208) and 44% (38/87) of patients with CrCL ≤120 mL/min, and >120 mL/min, respectively. Colistin methanesulfonate sodium (CMS) and colistin clearances were strongly dependent on CrCL. High colistin exposure to MIC ratio was associated with increased hazard of death in the multivariate analysis (adjusted hazard ratio (95% CI): 1.07 (1.03–1.12)). Other significant predictors included SOFA score at baseline (HR 1.24 (1.19–1.30) per score increase), age and Acinetobacter or Pseudomonas as index pathogen. Discussion: The population pharmacokinetic model predicted that >90% of the patients had colistin concentrations >2 mg/L at steady state, but only 66% at 4 hr after start of treatment. High colistin exposure was associated with poor kidney function, and was not related to a prolonged survival.